The effects of emotional intelligence, rewards and recognition, and workload on work engagement among academic staff in a Malaysian private university - Ng, Jun Ming; Tan, Keng Han; Wong, Ka Kin; Yeoh, Wei Loon (2023)
Academic staff at universities are essential to every country’s development. In order to achieve clearly stated objectives relating to program enhancement, recruitment and retention, and student learning outcomes, they coordinate the work of department heads. It was important to maintain their work engagement. The purpose of this research is to identify the effects of determinants on work engagement among academic staff in a Malaysian private university. It will also help the academic staffs and readers to have more understanding about the factors that will affect the work engagement. Quantitative research was used for this research by using self-administered questionnaire. The design of this research is cross-sectional design. A total of 285 questionnaires were collected from UTAR Kampar and UTAR Sungai Long using simple random sampling method. The result shows that workload is not significantly correlated with work engagement. It is important to have training and support in better understand and manage emotions. Besides that, employees should feel recognized and appreciated for their contributions. Furthermore, Workload is not an important factor affecting work engagement and other factors should be considered for future research.